Insights into the evolutionary history of the most skilled tool-handling platyrrhini monkey: Sapajus libidinosus from the Serra da Capivara National Park - Thaynara Lima; Bibiana Fam; Gustavo Medina Tavares; Tiago Falótico; Camila Cantele; Lucca Fanti; Luane Landau; Lucas Henriques Viscardi; Pedro Vargas-Pinilla; Ossman Barrientos-Diaz; Alcides Pissinatti; Vinicius A. Sortica; et al. (Genetics and Molecular Biology, 2023)
Abstract Sapajus libidinosus members of the Pedra Furada group, living in the Serra da Capivara National Park, use stone tools in a wider variety of behaviors than any other living animal, except humans. To rescue the evolutionary history of the Caatinga S. libidinosus and identify factors that may have contributed to the emergence and maintenance of their tool-use culture, we conducted fieldwork seasons to obtain biological samples of these capuchin monkeys. UsingCYTBsequences, we show a discrete but constant population growth from the beginning of the Holocene to the present, overlapping the emergence of the Caatinga biome. Our habitat suitability reconstruction reports the presence of plants whose hard fruits, seeds, or roots are processed by capuchins using tools. TheS. libidinosusindividuals in the Caatingawere capable of dynamically developing and maintaining their autochthonous culture thanks to: a) cognitive capacity to generate and execute innovation under selective pressure; b) tolerance favoring learning and cultural inheritance; c) an unknown genetic repertoire that underpins the adaptive traits; d) a high degree of terrestriality; e) presence and abundance of natural resources, which makes some places “hot spots” for innovation, and cultural diversification within a relatively short time.